Comparing the effectiveness of virtual reality and video modelling as an intervention strategy for individuals with Autism Spectrum Disorder: Brief report. (3rd April 2018) - Fitzgerald, Emily; Yap, Hui Kee; Ashton, Charlotte; Moore, Dennis W; Furlonger, Brett; Anderson, Angelika; Kickbush, Richard; Donald, James; Busacca, Margherita; English, Derek L
ABSTRACT: The increasing numbers of individuals diagnosed with Autism Spectrum Disorder (ASD) has foreshadowed a greater need for effective intervention procedures to aid learning. Purpose: This study compared the effectiveness of video modelling (VM) and virtual reality (VR) for teaching adults with ASD. Methods: Using an alternating treatments design without baseline two participants completed paper folding projects of varying difficulty following exposure to either VM or VR task modelling. The rate of learning (ROL) determined treatment effectiveness. Results: One participant reached mastery criterion for the intermediate project on the 5th trial with both VR and VM (i.e. equal ROL). The other achieved mastery by the 6th trial of VM, but did not attain mastery in VR. Both participants reported enjoying both procedures. Conclusions: The results suggest that VM was more effective than VR in facilitating learning. Implications for future research are discussed.